Two-person second-order games, part 2: restructuring operations to reach a win-win profile - Larbani, Moussa; Yu, Po Lung (Springer, 2009)
In Part 1 of the paper, using habitual domains theory and finite Markov chain theory, we have introduced a new model for describing the evolution of the states of mind of players over time, the two-person second-order game. The concepts of focal mind profile as well as the solution concept of win-win mind profile have been introduced as solution concepts for these games. In Part 2 of the paper, we address the problem of restructuring a game where the focal profile (1, 1) is not reachable or is not a win-win profile into a game where the profile (1, 1) is a reachable win-win profile. Precisely, under some reasonable assumptions, we derive the possibility theorem that it is always possible to reach a win-win mind profile in a two-person second-order game.Moreover, we provide practical operations for restructuring games for reaching a win-win profile.